Asymmetric Decentralization: Efforts to Maintain a Balance of Power between the Center and the Regions - Sundawa Bahtiar (Jurnal Multidisiplin Sahombu, 2025)
This study discusses the concept of asymmetric decentralization as a strategy to maintain the balance of power between the central and regional governments within Indonesia's governance system. Asymmetric decentralization grants different authorities to certain regions based on their unique geographical, social, economic, and political conditions. The aim of this research is to analyze how the implementation of asymmetric decentralization can strengthen regional autonomy without weakening national integration. The method used is a qualitative approach, employing literature review and policy analysis as data collection techniques.The findings of this study indicate that asymmetric decentralization in Indonesia is an effective solution for maintaining the balance of power between the central and regional governments. Through the provision of special autonomy to specific regions such as DKI Jakarta, Yogyakarta, Aceh, Papua, and West Papua, the government is able to accommodate the historical, cultural, and social uniqueness of each area. The implementation of this decentralization has proven to increase public participation, strengthen local identity, and promote the efficiency of regional governance. However, its success is highly dependent on clear regulations, institutional capacity, and consistent political and social support.